Auditory and non-auditory effects of consistent-use of mobile- telephone in Ibadan-Oyo State, Nigeria (2020)
Consistent exposure to sound generated by mobile phone have continued to pose threat on the human hearing functions. Adolescents are more likely than any other group to utilize the device for music playing functions, continued calls and other numerous functions. Thus, this study therefore, investigated the auditory and non- auditory effect of consistent-use of mobile telephone among adolescents in Ibadan Metropolis. The study adopted an ex-post facto research design. The sample of the study comprised 500 participants purposively selected. Data were analyzed using percentage, frequency and chi-square. The findings indicated that 11% of the participants had a notched hearing pattern, while 46.6% had a rising hearing pattern. 14.6%> of the participants claimed having ear pain after the use of mobile phone for calls and other listening purposes, while 12.6 % claimed having headache after prolong use of mobile telephony for music playing functions. The findings indicated that a number of the participants experienced both auditory and non-auditory problems due to consistent exposure to noise emanated from mobile phone. Based on the findings, it was recommended that prolong use of mobile phone especially for listening purpose and music playing functions should be reduced. Also, awareness campaigns on the dangers of consistent-use of mobile telephone should be instituted.